Proceedings of the 2nd International Workshop on Science of Smart City Operations and Platforms Engineering 2017
DOI: 10.1145/3063386.3063767
|View full text |Cite
|
Sign up to set email alerts
|

Optimal detection of faulty traffic sensors used in route planning

Abstract: In a smart city, real-time tra c sensors may be deployed for various applications, such as route planning. Unfortunately, sensors are prone to failures, which result in erroneous tra c data. Erroneous data can adversely a ect applications such as route planning, and can cause increased travel time. To minimize the impact of sensor failures, we must detect them promptly and accurately. However, typical detection algorithms may lead to a large number of false positives (i.e., false alarms) and false negatives (i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…We obtain the performance metrics and . Please note that more complex regression algorithms (e.g., Gaussian Processes [ 24 ]) can be used as well; however, we obtained satisfactory result with a simple linear regression model.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We obtain the performance metrics and . Please note that more complex regression algorithms (e.g., Gaussian Processes [ 24 ]) can be used as well; however, we obtained satisfactory result with a simple linear regression model.…”
Section: Discussionmentioning
confidence: 89%
“…Please note that this approach is particularly applicable to traffic networks as there are usually many redundant sensors in the network. The function can then be obtained using suitable machine learning regression algorithm such as deep neural networks [ 23 ], Gaussian Processes [ 24 ], and many others [ 25 ]. Thus, for sensor s , we obtain the prediction as .…”
Section: Anomaly Detectionmentioning
confidence: 99%
“…Nonetheless, the complexity of the network structure and its management pose high risks for data integrity. To combat this, Ghafouri et al [150] proposed an effective detector for inspecting sensor and communications failures to ensure data integrity in the smart city. The detector utilizes the Gaussian processes for optimization, as well as an approach for computing optimal parameters.…”
Section: ) Adversarial Learning In the Data Collection Phasementioning
confidence: 99%
“…Evaluating the proposed detector on the OpenTripPlanner platform, the results showed that the detector could reliably increase data integrity in the smart city. Furthermore, Ghafouri et al [151] proposed a general framework that considered attacks on a subset of sensors in CPS, with specific emphasis on overcoming the limitations of their prior work [150]. This framework consists of a general anomaly detection module that predicts a measurement for each sensor and leverages three different regression models: linear, neural network, and combined.…”
Section: ) Adversarial Learning In the Data Collection Phasementioning
confidence: 99%
“…The underlying assumption in this process is that the prior distribution of the regression function is considered to be a multivariate Gaussian distribution. By calculating the covariance matrix for the labeled data and covariance vector between labeled and new test data points and taking the measurement noise into account, the prediction result for the test data points can be obtained [Ghafouri, Laszka, Dubey, and Koutsoukos (2017)]. In this work, we have used Radial Basis Function (RBF) as the kernel.…”
Section: Prediction Using Gaussian Process Regressionmentioning
confidence: 99%